The Impact of Language and Literature in Promoting Social and Religious Values: An Analytical Study in Cultural and Educational Dimensions - Jawad, Asst.L.. Safaa Karim Jawad; Kadhim, Asst.L. Atiaf Jawad Kadhim (Sulaimani Journal for Humanities, 2026)
Language is considered one of the most important tools of human communication, as it can transcend its role as a means of conveying ideas to become an essential element in shaping cultural identities. Losing language means losing part of cultural identity and individual and collective feelings. Language is not just a collection of words, but rather expresses values, traditions and beliefs that constitute human nature. When an individual speaks in his mother tongue, he expresses his vision of the world and his value system through words and terms that are linked to his history and traditions. Therefore, the concept of linguistic identity and cultural identity are closely intertwined, making language present in all life experiences. Language can be said to shape and highlight identity at the same time, as speaking a certain language is considered an expression of belonging to a certain cultural group. Moreover, language contributes to conveying social and religious values, which allows for understanding the relationship between human thought and cultural phenomena. Therefore, this study opens new horizons in understanding the role of language as a means of conveying cultural and spiritual passports, which enhances the importance of preserving languages and appreciating cultural diversity. Ultimately, language remains an effective tool in shaping cultural identity and strengthening social ties in society, making its study necessary to understand the basics of human life. Language and literature are essential elements in shaping human identity, as they allow individuals to communicate and exchange ideas and feelings. The importance of language as a means of communication lies in its ability to convey messages between individuals and facilitate understanding between them, which contributes to building social and cultural ties. Without language, a person remains unable to express his needs and desires, which leads to a lack of mutual understanding. The study was divided into three axes: The first axis dealt with language as a tool for conveying moral values within societies. The second axis dealt with examples from Arabic and Islamic literature on promoting values. The third axis: It was a comparative study between cultures (comparing language and literature in promoting values in different cultures) The study concluded that language is an integral part of shaping cultural and religious identity within, as it works to build common values. It also confirms that sacred texts and religious discourses use languages as they still support their values Language also contributes to shaping cultural identity within Canada, where it is effective for its social and societal values. It also studies that sacred texts and religious discourses rely on a specific language to promote those values. Language works to build cultural identity and shape human values, and societal literary values reflect concepts of tolerance and justice. It is also necessary to study the importance of academic literary texts in shaping collective consciousness. Through this research, we clearly confirmed that there is an importance for language and literature in building societal presentations, and that we highlight the role of traditions that our cultural culture can support in these values. Understanding the compatibility between language and literature on the one hand, and social and religious values on the other hand, can continue to develop an effective way to promote understanding and tolerance in societies.
Keywords: language and literature; moral values; cultural values